Experiment and Analysis of Termination Robustness Design for 1200 V 4H-SiC MOSFET - Mengyuan Yu; Yi Shen; Hongping Ma; Qingchun Zhang (Nanomaterials)
This study investigates the degradation mechanisms of 1200 V SiC MOSFETs during High-temperature Reverse Bias (HTRB) reliability testing, focusing on breakdown voltage (BV) reduction. Experimental results reveal that trapped charges at the SiC/SiO2 interface in the termination region alter electric field distribution, leading to premature breakdown. To address this issue, an optimized termination structure is proposed, incorporating reduced spacing between adjacent field rings and additional outer rings. TCAD simulations and experimental validation demonstrate that the improved design stabilizes BV within 2% deviation during 1000 h HTRB testing, which significantly enhances termination robustness.